A price paid? A review of the research on the impact of investigating serious crime on the wellbeing of police staff. (March 2022) - Cartwright, Ashley; Roach, Jason
Research pertaining to the wellbeing of police focuses on the job at a macro level, neglecting that policing is an occupation made up of thousands of roles. The needs of staff in various roles differs according to the situations that they are exposed to. This paper provides a review of the literature pertaining to the impact of criminal investigation on employees' wellbeing. Three discernible categories regarding the wellbeing of criminal investigators are revealed and the paper demonstrates that criminal investigation has a negative effect on the wellbeing of staff. The paper concludes with recommendations for future research, training and support.